Design of Online Electric Power Monitoring For Street Vendors - Sri Rahayu, Endang; Puteri Nurul Magfirah; Reza Diharja (Faculty of Engineering, Universitas Brawijaya, 2024)
Street vendors are merchants who sell their goods on the sidewalk in front of shops or along the roadside. The common selling locations are typically on the front porch of a shop, and they obtain electricity by paying a rental fee to the owner. Owners of these shopfront spaces, providing the electrical supply, still employ conventional payment systems based on agreements between the owner and the user. The advancement of Internet of Things (IoT) technology has begun to support automatic and more accurate power monitoring systems. The objective of this research is to develop an online power monitoring system for street vendors based on RFID sensors and Telegram. It relies on the ESP32 microcontroller as the control system and the PZEM-004T sensor to measure current, voltage, and total power consumption. The implementation results show a measurement accuracy level of 99.1% for voltage, 99.66% for current, 91% for power, and 100% for energy. Purchasing, recharging, and monitoring of electrical energy were successfully conducted through the Telegram Bot. Additionally, the Telegram Bot successfully sends alerts in case of power leaks and when the electricity token is running out. The error rate in the measurement and monitoring of electrical energy used in the system is 0%.